Application of Multilinear Regression Analysis to Analyze the Effectiveness of Employee Performance in the Banking Industry - Syafrida Damanik; Putra, M. Umar Maya; Siburian, Mian Agus Nobel (Yayasan Gema Bina Nusantara, 2024)
The purpose of this research is to determine the influence of the recruitment and selection process on employee performance at PT. Bank Perkreditan Rakyat Duta Paramarta Medan. The population in this research is all employees of PT. Bank Perkreditan Rakyat Duta Paramarta Medan, totaling 33 people with saturated sampling. This type of research is quantitative. Quantitative research is research that aims to determine the degree of relationship and pattern or form of influence between two or more variables. Through this research, a theory will be built those functions to explain, predict, and control a phenomenon. Data collection techniques in this research were observation, interviews, questionnaires, and documentation. Meanwhile, the data analysis method is quantitative and multiple linear regression with hypothesis testing using t test analysis, the F test, and the coefficient of determination (R2). The results of the multiple regression analysis are Y = 3.696 + 0.393X1+0.465X2, which shows an increase in the recruitment process on employee performance by 0.393 units and selection by 0.465 units. Meanwhile, the results of the partial test (t test) show that there is a positive and significant influence of the recruitment process on employee performance with t-count = 3.672 > t-table 1.697 at α = 0.01 and the selection variable has a positive and significant effect of selection on employee performance where it can be seen that the t-count value =3.69 2> t-table = 1.697 at α = 0.01. The coefficient of determination (R2) with adjusted R2 is 0.709, meaning that the recruitment and selection variables can explain the employee performance variable by 70.9%, while the remaining 29.1% is explained by other variables outside the model. So, it can be concluded that there is a positive and significant influence of the recruitment and selection process on employee performance at PT. Bank Perkreditan Rakyat Duta Paramarta Medan.